Is Neck Circumference A Better Measure for Determining Obesity? A Cross-Sectional Analytical Study to Assess Its Validity in Type II Diabetes Mellitus Patient - Gowthaman Sankar; Meriton Stanly A; Indraja Katam; Arun Raja (Medsci Publications, 2022)
Introduction: Several anthropometric measurements like Body mass index (BMI), skin fold thickness, Waist circumference (WC), waist-height ratio (WHtR), and Waist hip ratio (WHR) are available for diagnosing obesity at the population level. But each of them has its disadvantage as well. Neck circumference, which has been the recent anthropometric tool of interest can be used as an alternative to these measurements. Objective: To determine the validity of neck circumference as an anthropometric parameter of obesity and to estimate the cut-off points for obesity in type II diabetes mellitus patients. Material & Methods: This analytical cross-sectional study was done among 141 Type II diabetes patients attending rural and urban health training center Non-communicable disease clinic of Sri Ramachandra Institute of higher education and research, Chennai. After obtaining informed consent, their anthropometric measurements like NC, BMI, WC, HC, and WHR was measured. Results:  Neck circumference ≥36.5cm in males and ≥33.2cm in females is conceivably the perfect cut-off point for diagnosing overweight/Obesity in Type II diabetes mellitus. Conclusion: This analytical study deduced that NC is a valid anthropometric measurement for diagnosing obesity among Type II diabetes mellitus with plausible sensitivity and specificity.